Curcumin Inhibits Joint Contracture through PTEN Demethylation and Targeting PI3K/Akt/mTOR Pathway in Myofibroblasts from Human Joint Capsule. (14th August 2019) - Zhuang, Ze; Yu, Dongjie; Chen, Zheng; Liu, Dezhao; Yuan, Guohui; Yirong, Ni; Sun, Linlin; Liu, Yuangao; He, Ronghan; Wang, Kun
Abstract : Joint contracture is increasingly regarded as a clinical problem that leads to irreversible dysfunction of the joint. It is a pathophysiological process following joint injury, which is marked by the activation of myofibroblasts. There is currently no effective treatment for the prevention of joint contracture. Curcumin is a polyphenol pigment extracted from turmeric, which possesses anti-inflammatory, antioxidative, and antitumor properties. In the present study, we demonstrated that curcumin exerts a protective effect against joint contracture via the inhibition of myofibroblast proliferation and migration in a time- and concentration-dependent manner. Moreover, we indicated that phosphatase and tension homolog (PTEN) was downregulated in myofibroblasts in vitro and in the contracture capsule tissues of patients in vivo . Additionally, western blot analysis revealed a negative correlation between the expression levels of PTEN and the fibrosis marker protein alpha smooth muscle cell actin. Methylation-specific PCR results suggested that curcumin was able to demethylate PTEN in a similar manner to the demethylation agent 5-azacytidine, increasing PTEN expression and further inhibiting phosphoinositide 3-kinase/protein kinase B /mammalian target of rapamycin signaling. In conclusion, our data illustrate part of the mechanism of curcumin inhibition in joint contracture. These results support the hypothesis that curcumin may potentially be used as a novel candidate for the treatment of joint contracture.